2010
DOI: 10.1111/j.1365-246x.2010.04761.x
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inversion of microtremor array dispersion data in southwestern British Columbia

Abstract: S U M M A R YThis paper applies Bayesian inversion, with evaluation of data errors and model parametrization, to produce the most-probable shear-wave velocity profile together with quantitative uncertainty estimates from microtremor array dispersion data. Generally, the most important property for characterizing earthquake site response is the shear-wave velocity (V S ) profile. The microtremor array method determines phase velocity dispersion of Rayleigh surface waves from multi-instrument recordings of urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…Note also that it has been shown that parameter estimation uncertainty can be under-estimated if data error covariance is not properly taken into account. 33,48 B. Inversion results for the selected model Once the model parametrization has been chosen using BIC analysis, the PPD can be estimated. Figure 7 presents marginal probability densities for each individual parameter.…”
Section: A Model Selection and Data Error Estimationmentioning
confidence: 99%
“…Note also that it has been shown that parameter estimation uncertainty can be under-estimated if data error covariance is not properly taken into account. 33,48 B. Inversion results for the selected model Once the model parametrization has been chosen using BIC analysis, the PPD can be estimated. Figure 7 presents marginal probability densities for each individual parameter.…”
Section: A Model Selection and Data Error Estimationmentioning
confidence: 99%
“…The first arrival traveltimes can be picked on the same seismic gathers used for dispersion curve extraction (Figure 1a). Different shots along the seismic line are used to retrieve the complete P-wave first arrival data set and to improve the dispersion curve quality through stacking in spectral domain (Neducza, 2007).…”
Section: Methods Datamentioning
confidence: 99%
“…for j < i (after Molnar et al, 2010). Here, we allow σ 0 ¼ σ L ∕jσ L j 1∕2 for a Laplacian model and σ 0 ¼ σ G for a Gaussian model, as previously.…”
Section: Data-error Covariancementioning
confidence: 97%
“…Consequently, the calculation proceeds by droppingĈ m from equation 9. The results of this are shown in Figure 9, The second approach to quantifying model uncertainty uses a Monte-Carlo method described as a Fast Gibbs Sampler by Molnar et al (2010), following on from the discussions in Dosso (2002) and Dosso and Wilmut (2002), to which the reader is heartily referred. The Fast Gibbs Sampler is a Monte-Carlo Markov-Chain analysis that in practical usage is very closely related to simulated annealing, although its theoretical basis is less so.…”
Section: Model Uncertaintiesmentioning
confidence: 99%